Enriching rice grain zinc through zinc fertilization and water management - Tuyogon, D.S.J.; Impa, S.M.; Castillo, O.B.; Larazo, W.; Johnson-Beebout, S.E. (Wiley, 2016)
Core Ideas Rice grain‐Zn concentration increased with more aerobic soil conditions. Fertilizer‐Zn applied to soil had limited effect on rice grain‐Zn concentration. Rice paddy water management affected soil redox potential and DTPA‐extractable Zn. Combined water and Zn management are useful for agronomic Zn biofortification. Agronomic biofortification was not sufficient to meet rice Zn nutrition targets.Rice grain‐Zn concentration increased with more aerobic soil conditions.Fertilizer‐Zn applied to soil had limited effect on rice grain‐Zn concentration.Rice paddy water management affected soil redox potential and DTPA‐extractable Zn.Combined water and Zn management are useful for agronomic Zn biofortification.Agronomic biofortification was not sufficient to meet rice Zn nutrition targets.Increasing rice (Oryza sativa) grain‐Zn concentration is important for achieving improved human nutrition. Our objective was to understand how agronomic management practices, including water management and fertilizer‐Zn application rate and timing, affect plant growth, grain‐Zn concentration, and yield of rice genotypes. In a series of four‐field experiments over three seasons, we tested multiple combinations of water management techniques and fertilizer‐Zn application techniques. The use of alternate wetting and drying (AWD) water management increased (p < 0.001) soil redox potential and diethylene triamine pentaacetic acid (DTPA)‐extractable soil Zn compared with continuous flooding (CF) in the 0‐ to 2‐cm soil depth, but not always in the 2‐ to 10‐cm depth. On average, AWD grain‐Zn concentration increased 9% over CF without any yield penalty. Fertilizer‐Zn application increased DTPA‐extractable Zn only in the top soil layer and only temporarily, with a corresponding increase in grain‐Zn concentration only at rates > 10 kg Zn ha−1. Different timings of fertilizer‐Zn application (from basal to flowering) had no effect on grain‐Zn concentration or yield. Overall, our results indicated that AWD had a consistent and larger positive effect than fertilizer‐Zn application on grain‐Zn concentration. However, the increase in grain‐Zn concentration due to fertilizer‐Zn or water management was small, up to 2 mg Zn kg−1 brown rice, implying that improved agronomic management alone is not sufficient to meet the target increase of at least 10 mg Zn kg−1, but is a useful complementary strategy for enhancing the performance of Zn‐enriched rice by improving soil‐Zn availability.